2013
DOI: 10.1073/pnas.1218986110
|View full text |Cite
|
Sign up to set email alerts
|

Transient formation of water-conducting states in membrane transporters

Abstract: Membrane transporters rely on highly coordinated structural transitions between major conformational states for their function, to prevent simultaneous access of the substrate binding site to both sides of the membrane-a mode of operation known as the alternating access model. Although this mechanism successfully accounts for the efficient exchange of the primary substrate across the membrane, accruing evidence on significant water transport and even uncoupled ion transport mediated by transporters has challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
84
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 57 publications
15
84
1
Order By: Relevance
“…This, or closely related conformational states, are poised to release both Na + and sugar through that passage, and consistent with a strict alternating-access mechanism, the X-ray structure exhibits a thick outer gate that occludes the substrate site from the extracellular space. Simulations of vSGLT have revealed that this outer gate is permeable to water, which crosses the transporter through the sugar binding site, and that water flow is modulated by the transient formation of an opening on the extracellular face of the transporter (18)(19)(20)(21). In 2 of our 21 simulations, the galactose escapes to the extracellular bulk through the same opening.…”
Section: Resultsmentioning
confidence: 83%
“…This, or closely related conformational states, are poised to release both Na + and sugar through that passage, and consistent with a strict alternating-access mechanism, the X-ray structure exhibits a thick outer gate that occludes the substrate site from the extracellular space. Simulations of vSGLT have revealed that this outer gate is permeable to water, which crosses the transporter through the sugar binding site, and that water flow is modulated by the transient formation of an opening on the extracellular face of the transporter (18)(19)(20)(21). In 2 of our 21 simulations, the galactose escapes to the extracellular bulk through the same opening.…”
Section: Resultsmentioning
confidence: 83%
“…Our findings also directly support the hypothesis by Baradaran et al (13) that water molecules may play an important role in providing protonic connectivity between key amino acids. Interestingly, the functional significance of transient hydration in the function of structurally related membrane transporters was recently also discussed by Li et al (35). 5.…”
Section: Resultsmentioning
confidence: 92%
“…17−19 A clearer picture of Na + −glucose interactions could be of use in efforts toward a molecular understanding of how these enzymes function, which is a topic of current interest. 20 Glucose conformations in the aqueous phase have been extensively studied, providing a baseline for the present study of aqueous glucose interactions with inorganic salt. NMR experiments have revealed the ratio of β-to α-glucose in aqueous solution to be approximately 2 to 1, with the ratio sensitive to temperature, and have demonstrated that the glucose molecules predominantly adopt the equatorial chair pyranose ring conformation ( 4 C 1 ).…”
Section: ■ Introductionmentioning
confidence: 99%